Florentine Renaissance Resources. Online Tratte of Office Holders 1282-1532, Ed. by D. Herlihy, R. Burr Litchfield, A. Molho, R. Barducci, 2000. Online Catasto of 1427, Ed. by D. Herlihy, C. Klapisch-Zuber, Vers. 1.2., Brown University, Providence, R.I. - Bicchierai, Marco (Reti Medievali Rivista, 2002)
Florentine Renaissance Resources. - Online Tratte of Office Holders 1282-1532, Edited by David Herlihy, R. Burr Litchfield, Anthony Molho and Roberto Barducci <http://www.stg.brown.edu/projects/tratte/>, 2000 - Online Catasto of 1427, Edited by David Herlihy, Christiane Klapisch-Zuber, Version 1.2., Brown University, Providence, R.I. <http://www.stg.brown.edu/projects/catasto/>, 1996